Oculoectodermal syndrome: report of a new case with a broad clinical spectrum - Aslan, Deniz; Moog, Ute (American journal of medical genetics, 2014)
Oculoectodermal syndrome (OMIM 600268) is rare and characterized by aplasia cutis congenita, epibulbar dermoids, and other abnormalities. We report herein on a newly recognized patient with oculoectodermal syndrome, which is the 19th reported patient with OES. The boy aged six years demonstrated a broad clinical spectrum of this condition, including aplasia cutis congenita, epibulbar dermoids, hyperkeratotic papule, mildly enlarged cisterna magna, and an enlarged fluid space in the quadrigeminal cistern, suggesting a cyst. He also manifested anomalies not reported associated with this disorder, including systematized epidermal nevus following Blaschko's lines, hypopigmented skin lesions, and mild digital anomaly. © 2014 Wiley Periodicals, Inc.
Gesehen am 16.10.2020